Phytochemistry of Indian Medicinal Plants: Therapeutic Potential and Global Relevance - Gaur, Arvind (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Indian medicinal plants have long been central to traditional healthcare systems such as Ayurveda, offering a rich source of bioactive compounds known as phytochemicals. These naturally occurring constituents—such as alkaloids, flavonoids, terpenoids, saponins, tannins, and phenolics—exhibit a wide range of therapeutic effects, including anti-inflammatory, antioxidant, antimicrobial, antidiabetic, and anticancer activities. Their diverse pharmacological properties form the scientific basis for many traditional remedies and have attracted growing global interest. In recent years, advancements in phytochemical research have highlighted the potential of these compounds in modern drug discovery and integrative medicine. With increasing demand for plant-based therapeutics and a shift toward holistic healthcare, Indian medicinal plants offer valuable opportunities for innovation in global health. This paper explores key phytochemical classes, their therapeutic potential, and their relevance in both traditional and contemporary medical contexts.